Successful percutaneous femoral extraction of a detached tricuspid valve‐in‐valve balloon delivery system. Issue 8 (10th July 2019) - Sidhu, Baldeep S.; Gould, Justin; Sieniewicz, Benjamin; Porter, Bradley; Prendergast, Bernard; Redwood, Simon; Rinaldi, Christopher A.
Abstract: We shall discuss a patient who underwent a tricuspid valve‐in‐valve implantation for a failing bioprosthetic valve replacement. The procedure was complicated by detachment of the valve deployment apparatus which was removed in its entirety, using percutaneous extraction techniques. We believe this was the first ever case to report such a complication. Abstract : We shall discuss a patient who underwent a tricuspid valve‐in‐valve implantation for a failing bioprosthetic valve replacement. The procedure was complicated by detachment of the valve deployment apparatus which was removed in its entirety, using percutaneous extraction techniques. We believe this was the first ever case to report such a complication.